Microbial ecology of acid tropical soils - Ayanaba, A.; Omayuli, A.P.O. (1975)
Microbial populations of 11 Nigerian soils are reported. Four soils from the dry forest zone of Nsukka, East Central State, are characterized by few algae, nitrifiers, denitrifiers, and aerobic cellulose decomposers. Four soils from four northern States in the Guinea savanna have abundant bacteria and algae but in none of these soils do Azotobacter or Beijerinckia exceed 100 bacteria/g soil. Three soils from the dry forest zone of Ibadan, Western State, contain normal densities of the microbes examined. Populations of fungi and actinomycetes in the 11 soils vary little. Acidity has a great influence on the densities of the microbes examined. No conclusions can be drawn on the relation of temperature, soil type, or vegetation to the densities of the microbes examined.